Cellular activation status in femoral shaft fracture hematoma following different reaming techniques – A large animal model. Issue 12 (17th March 2022) - Teuben, Michel Paul Johan; Halvachizadeh, Sascha; Kalbas, Yannik; Qiao, Zhi; Cesarovic, Nikola; Weisskopf, Miriam; Teuber, Henrik; Kalbitz, Miriam; Cinelli, Paolo; Pfeifer, Roman; Pape, Hans‐Christoph
Abstract: The local inflammatory impact of different reaming protocols in intramedullary nailing has been sparsely investigated. We examined the effect of different reaming protocols on fracture hematoma (FH) immunological characteristics in pigs. To do so, a standardized midshaft femur fracture was induced in adult male pigs. Fractures were treated with conventional reamed femoral nailing (group RFN, n = 6); unreamed femoral nailing (group UFN, n = 6); reaming with a Reamer Irrigator Aspirator device (group RIA, n = 12). Animals were observed for 6 h and FH was collected. FH‐cell apoptosis and neutrophil receptor expression (Mac‐1/CD11b and Fc γ RIII/CD16) were studied by flow cytometry and local temperature changes were analyzed. The study demonstrates that apoptosis‐rates of FH‐immune cells were significantly lower in group RIA (3.50 ± 0.53%) when compared with non‐RIA groups: (group UFN 12.50 ± 5.22%, p = 0.028 UFN vs. RIA), (group RFN 13.30 ± 3.18%, p < 0.001, RFN vs. RIA). Further, RIA‐FH showed lower neutrophil CD11b/CD16 expression when compared with RFN (mean difference of 43.0% median fluorescence intensity (MFI), p = 0.02; and mean difference of 35.3% MFI, p = 0.04, respectively). Finally, RIA induced a transient local hypothermia and hypothermia negatively correlated with both FH‐immune cell apoptosis and neutrophil activation. In conclusion, immunologic changes observed in FH appear to be modified by certain reaming techniques. Irrigation during reaming was associated with transient local hypothermia, decreased apoptosis, and reduced neutrophil activation. Further study is warranted to examine whether the rinsing effect of RIA, specific tissue removal by reaming, or thermal effects predominantly determine local inflammatory changes during reaming.